An implementation of domains and keys in SQL : a thesis presented in fulfilment of the requirements for the degree Master of Philosophy at Massey University - Alexander, John Lindsay (Massey University, 1987)
The relational Data Base Management System model has steadily acquired increasing acceptance over the years since it was first introduced in 1970, yet few – if any – of the many relational products currently available support the fundamental concepts of domains and the integrity constraints of primary and foreign keys. Over more recent years the SQL Relational Database Sub-Language has found most favour among users and vendors alike, and a standard for SQL has recently been produced. This standard provides no support for domains or foreign keys, and only indirect support for primary keys. This thesis first reviews MURDER, the relational dabatase management system used for teaching purposes at Massey, and then describes an implementation of the domain and key concepts, highlighting some of the problem areas still to be resolved. Also described is an implementation of the query and update facilities of SQL, including some extensions which it is claimed increase its functionality. Finally, refinements to the language definition are suggested, to remove some redundancies and ambiguities.
Keywords: Relational databases; SQL (Computer program language)